On The Emergence of Uzbek Hemeronymy and First Examples - Yuldashev Otabek Toshpulat ugli (Zien Journals, 2022)
The article describes the first examples of hemeronymy of the Uzbek language – the linguistic analysis of the names of newspapers published by the representatives of the Jadid movement, the views of the Jadids regarding the newspaper
Keywords: Jadid; jadidist movement; hemeronym; onomastic microscope